2010
DOI: 10.1111/j.1439-0396.2010.01092.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementation with digestible undegradable protein in late pregnancy on ewe colostrums production and lamb output to weaning

Abstract: The aim of this study was to investigate the effects of supplementation with digestible undegradable protein (DUP) in diet during late pregnancy on colostrum production, lamb survival and growth. For 3 weeks prior to lambing, 41 Afshari ewes were assigned at random to three dietary treatments, namely a control (CDUP), moderate (MDUP) and high (HDUP) DUP group. The ewes (n = 14) in CDUP group were fed a protein maintenance level for pregnant ewes [83 g metabolizable protein (MP)/kg dry matter (DM)], while ewes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
(44 reference statements)
3
13
0
Order By: Relevance
“…This is contrary to the results observed in yr 1 of the current study, in which there was no difference in gestation length due to the MP intake of the dam during late gestation. Similar to our results, Amanlou et al (2011) reported that gestation length was not altered by maternal MP supplementation in ewes during late gestation. Gestation length could not be measured accurately in yr 2 due to the lack of breeding mark observations on a daily basis.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This is contrary to the results observed in yr 1 of the current study, in which there was no difference in gestation length due to the MP intake of the dam during late gestation. Similar to our results, Amanlou et al (2011) reported that gestation length was not altered by maternal MP supplementation in ewes during late gestation. Gestation length could not be measured accurately in yr 2 due to the lack of breeding mark observations on a daily basis.…”
Section: Discussionsupporting
confidence: 92%
“…Calves born to cows that were supplemented with CP during late gestation were heavier at weaning than calves born to cows that were not supplemented (Stalker et al, 2006). However, Amanlou et al (2011) observed no effects of maternal MP supplementation (114 and 124% of MP requirements) on lamb weaning BW. Although there was a tendency for weaning weights to be linearly increased as MP in the diet increased, this tendency was not observed in yr 2.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations